The Strength of Two Hands: Conflicting Stakeholder Pressures and Corporate Philanthropic Giving. (May 2020) - Zhang, Liang; Zhang, Zhe; Jia, Ming; Ren, Yeyao
ABSTRACT: We develop a stakeholder framework that examines how firms respond to the conflicting demands that arise from governments and investors in the context of corporate philanthropic giving. We argue that firms that experience such conflict exhibit a decoupling response in philanthropic giving. Furthermore, we identify the boundary conditions of the relationship between the conflicting pressures and the decoupling response. Drawing on stakeholder salience literature, we argue that this relationship will be weakened when CEOs perceive government demands as more salient (such as those with a communist ideology) and when CEOs are less sensitive to investor claims (such as those with fewer career concerns). We find empirical support for our arguments using a sample of 8, 857 Chinese listed firms from 2006 to 2015. Our study contributes to the literature on stakeholder theory, decoupling, and corporate philanthropy.